Exploring novice teachers’ experiences in coping with adversities at a rural school in the Thabo Mofutsanyane district in COVID-19: A wellbeing programme - Masabata Dlhlamini (International Journal of Studies in Psychology)
This study explored how a wellbeing programme helps novice teachers cope with adversity at a rural school. It adopted a qualitative approach and case study research design. This study employed in-depth semi-structured interviews in data collection. Four novice teachers were selected to participate in the study from a rural school in the Thabo Mofutsanyane district, Free State Province, South Africa. It used thematic analysis to analyse qualitative data. The results revealed that novice teachers experienced a lack of cooperation, no sense of belonging, no warm welcome, conflict, discouragement, job dissatisfaction, and traumatised and ill-disciplined learners during the COVID-19 pandemic. There are various reasons why most of them find it difficult to cope with adversities at a rural school. This study recommended that the National Department of Basic Education create a policy allowing teachers to submit necessary documents needed by the administration of the department of basic education.